Anti-Ro52 Antibodies and Interstitial Lung Disease in Connective Tissue Diseases Excluding Scleroderma. (27th March 2012) - Ferreira, João Pedro; Almeida, Isabel; Marinho, António; Cerveira, Conceição; Vasconcelos, Carlos
Abstract : Introduction . The presence of anti-Ro52 antibodies has been reported in a wide variety of autoimmune diseases, particularly in myositis, scleroderma, and autoimmune liver diseases. Clinical significance of anti-Ro52 antibodies remains controversial, and studies are lacking for clarifying the association of anti-Ro52 with interstitial lung disease (ILD) in connective tissue diseases (CTD). Objectives . To determine if anti-Ro52 antibodies are associated with ILD in CTD other than scleroderma. Methods . Single-center, retrospective study based on immunoblotting panel analysis and patients clinical records. Results . In our connective tissue disease cohort, 162 patients had immunoblotting panels with anti-Ro52 reactivity analysis, 41 (25, 3%) had inclusion criteria. Among the 41 selected sera, 85.4% (n = 35 ) had anti-Ro52 reactivity. The prevalence of ILD in the positive anti-Ro52 antibodies was 71.4% (n = 25 ), and 16.7% (n = 1 ) in the negative anti-Ro52 group (P = 0.018 ). Overall sensitivity (96.2%), specificity (83.3%), positive (71.4%) and negative (83.3%) predictive values of anti-Ro52 antibodies to determine ILD in CTD is detailed in this study. Conclusion . Ro52 autoantibodies are associated with ILD in CTD excluding scleroderma. We suggest that the presence of anti-Ro52 reactivity in CTD should increase the clinician curiosity for the search of ILD.